Stress-dependent local oxidation of silicon - Evans, J.D.; King, J.R. (Society for Industrial and Applied Mathematics, 2017)
The two-dimensional isolation oxidation of silicon is considered for stress-dependent reaction and diffusion coefficients. The influence of such parameters is investigated numerically and asymptotically in the bird's beak problem and for curved geometries arising in the oxidation of cylindrical and spherical structures. In the bird's beak problem, the limit of large activation volume is described for a stress-dependent reaction coefficient, illustrating the significant growth retardation of the silicon/silicon oxide interface and reduced stresses in the silicon oxide. Novel high-order nonlinear evolution-type PDEs are derived and investigated using asymptotic and numerical techniques.